Heterogeneous double-activation catalysis: Rh complex and tertiary amine on the same solid surface for the 1, 4-addition reaction of aryl- and alkylboronic acids1. Issue 5 (28th May 2015) - Noda, Hiroto; Motokura, Ken; Chun, Wang-Jae; Miyaji, Akimitsu; Yamaguchi, Sho; Baba, Toshihide
<x xml:space="preserve">Abstract</x> Double-activation catalysis by a rhodium complex/tertiary amine catalyst for the 1, 4-addition of organoboronic acids was investigated.